2009
DOI: 10.1007/s00784-009-0347-4
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of persistent pockets in maintenance patients—a clinical study

Abstract: The aim of this study was to compare the short-term performance of a session of single photodynamic therapy (PDT) and of a conventional ultrasonic debridement (UST) in persistent pockets of maintenance patients. In a prospective, randomized, controlled, single-blind clinical study, patients with chronic periodontitis with at least two persistent pockets (>4 mm) were enrolled. They were treated either with UST (n = 29) or PDT (n = 25). Clinical and microbiological examinations were performed at baseline and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 39 publications
9
58
1
6
Order By: Relevance
“…Higher reduction of PD in the SRP + aPDT group at 1 month may have resulted from additional shrinkage in the inflamed pocket wall after reduction in microbial load achieved by PDT. The SRP + aPDT group again had an edge over SRP group at 3 months post treatment follow up, however, this time, the inter-group difference in PD reduction was statistically non-significant in accordance with studies by Chondros et al, 23 Al-Zahrani et al, 30 Polansky et al, 31 and Rühling et al 32 In contrast, various other clinical trials have reported significantly higher reduction of PD in patients receiving aPDT in addition to SRP. 9,33 However, their results cannot be compared with the present study as there were major differences in terms of study design, sample size, and frequency of aPDT application.…”
Section: Discussionsupporting
confidence: 82%
“…Higher reduction of PD in the SRP + aPDT group at 1 month may have resulted from additional shrinkage in the inflamed pocket wall after reduction in microbial load achieved by PDT. The SRP + aPDT group again had an edge over SRP group at 3 months post treatment follow up, however, this time, the inter-group difference in PD reduction was statistically non-significant in accordance with studies by Chondros et al, 23 Al-Zahrani et al, 30 Polansky et al, 31 and Rühling et al 32 In contrast, various other clinical trials have reported significantly higher reduction of PD in patients receiving aPDT in addition to SRP. 9,33 However, their results cannot be compared with the present study as there were major differences in terms of study design, sample size, and frequency of aPDT application.…”
Section: Discussionsupporting
confidence: 82%
“…17 In a similar study done by Ruhling et al on 25 patients using 636 nm diode laser photo synthesizer phenothiazine chloride, similar results were obtained. 18 Lui et al in 2011 in a clinical trial investigated 24 patients with chronic periodontitis. The patients were randomly divided into 2 groups: group 1-under SRP treatment and group 2-under SRP and PDT treatment (diode laser 940 nm for 3 days).…”
Section: Review Of Literaturementioning
confidence: 99%
“…14,15 During maintenance therapy, sites may [16][17][18] Diode laser-assisted periodontal therapy using photodynamic therapy was not superior to conventional mechanical debridement, 19 however photodynamic therapy was shown to be superior in eliminating pockets especially in single rooted teeth maintenance phase as seen by Campos et al 20 In our study, piezoelectric ultrasonic unit (EMS) was used to perform SRP. Chapper et al found that there was no significant difference found in treatment outcomes of ultrasonic scaling alone or ultrasonic scaling followed by hand scaling as the final step.…”
Section: Discussionmentioning
confidence: 70%